Correlation between structural data and spectroscopic studies of a new beta-diketonate complex with trivalent europium and gadolinium - Monteiro, Jorge H. S. K. [UNESP]; Adati, Renata Danielle [UNESP]; Davolos, Marian Rosaly [UNESP]; Vicenti, Juliano R. M.; Burrow, Robert A. (Royal Soc Chemistry, 2011)
This paper reports the study of structural and luminescence parameters of a seven-coordination compound containing beta-diketone butyl methoxy-dibenzoyl-methane (bmdm) and triphenylphosphine oxide (tppo), both acting as antennae. The complex was obtained by substitution of water molecules in the [RE(bmdm)(3)(H2O)(2)] precursor, where RE = Eu3+ or Gd3+. The structural data determined by X-ray monocrystal diffraction reveal that the compound crystallizes in a triclinic space group P (1) over bar and the coordination polyhedron is near a capped trigonal prism, with a symmetry site near a C-2v point group. The ground state geometry was determined using Sparkle/AM1 implemented in mopac2009 software, and compared with that obtained by monocrystal. The triplet (T) and singlet (S) levels were determined using INDO/S-CIS implemented in the Zindo software, the results obtained are very close to the experimental measurements. The intensity parameters Omega(2) and Omega(4) were calculated from emission spectrum. The high value of the Omega(2) parameter (37.2 x 10(-20) cm(2)) shows a highly polarizable environment around the europium ion and a high degree of covalence between the ligand and metal, showing that tppo molecules contribute to an increase in the covalence between the metal and ligand. The transfer rates show a predominance in the transfer process when compared with back transfer ones, with the main channel of transfer processes: T -> D-5(1) and T -> D-5(0).